2018
DOI: 10.1080/19420889.2017.1356956
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide treatment robustly protects from inherited mouse glaucoma

Abstract: Nicotinamide adenine dinucleotide (NAD) is a key molecule in several cellular processes and is essential for healthy mitochondrial metabolism. We recently reported that mitochondrial dysfunction is among the very first changes to occur within retinal ganglion cells during initiation of glaucoma in DBA/2J mice. Furthermore, we demonstrated that an age-dependent decline of NAD contributes to mitochondrial dysfunction and vulnerability to glaucoma. The decrease in NAD renders retinal ganglion cells vulnerable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 28 publications
7
56
0
1
Order By: Relevance
“…Further studies with larger cohorts are also required, as well as investigations in populations with various cultural dietary habits, to find out whether this deficiency is consistently associated with POAG and eventually with other forms of glaucoma. Finally, the convergence between recent studies showing that oral administration of nicotinamide prevents glaucoma in the DBA/2J mouse model 6,7,20 and our study on patients with POAG, opens promising therapeutic perspectives based on nicotinamide supplementation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Further studies with larger cohorts are also required, as well as investigations in populations with various cultural dietary habits, to find out whether this deficiency is consistently associated with POAG and eventually with other forms of glaucoma. Finally, the convergence between recent studies showing that oral administration of nicotinamide prevents glaucoma in the DBA/2J mouse model 6,7,20 and our study on patients with POAG, opens promising therapeutic perspectives based on nicotinamide supplementation.…”
Section: Discussionsupporting
confidence: 63%
“…Mitochondrial dysfunctions and decreased NAD content are hallmarks of aging in most organs 13,14 and many experimental studies, essentially performed on mouse models, have revealed that strategies based on NAD repletion effectively reverse age-related phenotypes and disorders 15,16 , such as those affecting the skeletal muscles 17 , the brain 18 , and the endothelium 19 . Recent studies on the DBA/2J mouse model of glaucoma, have further confirmed a dose-dependent protective effect of NAD repletion on the optic nerve, reaching a protection level of 93% at the highest nicotinamide dose tested (2000 mg/kg/day), despite a continuously elevated IOP 6,7,20 . More importantly, the age-dependent vulnerability of the RGCs in these mice is correlated with the decreased concentration of NAD in the retina.…”
Section: Discussionmentioning
confidence: 82%
“…d 2 ‐Nam has previously been shown to give 4.1 % 1 H polarisation using [IrCl(COD)(IMes)] in [D4]methanol under 3 bar p ‐H 2 . Nicotinamide has been previously used at high doses in humans whilst a more recent in vivo study of inherited mouse glaucoma showed potential neuroprotective effects . In this study, we prepared a sample containing [IrCl(COD)(IMes)] (5 m m ), d 2 ‐Nam (20 m m ) in 30 % [D6]ethanol in D 2 O and exposed it to 3 bar p ‐H 2 in a 65 G polarization transfer field.…”
Section: Resultsmentioning
confidence: 93%
“…Despite limited cell death being observed with this substrate, we would not envisage in vivo administration of the SABRE reaction mixture without first reducing the iridium content to below recommended exposure limits. [32] When [IrCl (COD)(d 22 -IMes)] was used as the catalyst, exposing the sample containing d 2 -Nam to p-H 2 in a 65 G polarization transfer field gave a 606-fold signal gain in the biocompatible solvent mixture. Upon replacing the IMes ligand with a caffeine derivative, the cytotoxicity profile did not change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation